Gender differences in latent classes of sleep quality in community-dwelling adults based on the Pittsburgh sleep quality index. Issue 8 (14th September 2019) - Chen, Xiaoyun; Fang, Yueyan; Liu, Xiaohua; Zhao, Di; Feng, Xiujuan; Li, Ping
ABSTRACT: This study investigated the latent classes of sleep quality based on the Pittsburgh Sleep Quality index (PSQI) in Chinese adults, and analyzed whether these latent classes differed between men and women. A total of 982 adults (age: 18–59 years) participated in the questionnaire survey, and the PSQI was used to assess sleep quality. Two latent classes of sleep quality were found in men, and the cut-off value of PSQI for predicting the poor sleep quality group was 6. Four latent classes were found in women, which were named 'good sleep', 'daytime dysfunction', 'inadequate sleep', and 'poor sleep', respectively. In women, the optimal cut-off values of the PSQI for predicting the poor and good sleep quality groups were 9 and 6, respectively. Women who were not included in the 'poor sleep' group but had a score not less than 2 in the 'sleep duration' or 'daytime dysfunction' dimensions of PSQI were classified into the 'inadequate sleep' group or the 'daytime dysfunction' group. The findings may benefit the identification of sleep problems and assist in more effective alleviation of these issues.